Qualitative and Comparative Analysis of Sharia vs. Conventional QRIS Usage - Mega Zhafarina Purwono (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital financial technology in Indonesia has been significantly shaped by the introduction of the Quick Response Code Indonesian Standard (QRIS) as a unified platform for electronic transactions. While conventional QRIS has gained widespread adoption due to its efficiency, interoperability, and institutional support, the emergence of QRIS Syariah introduces a new dimension by aligning digital payments with Islamic principles. This study employs a normative legal research method, relying on secondary sources from journals, books, and official reports, to provide a qualitative and comparative analysis of QRIS Syariah and conventional QRIS usage in Indonesia. The findings reveal that both systems share common adoption drivers, including perceived usefulness, trust, and social influence. However, QRIS Syariah adoption is uniquely characterized by religiosity and moral trust, which serve as decisive factors for consumers seeking Sharia-compliant financial practices. Conventional QRIS adoption demonstrates the importance of technological readiness, security, and behavioral incentives, while QRIS Syariah adoption highlights the need for religious legitimacy and targeted educational campaigns. The comparative analysis underscores that promoting financial inclusion in Indonesia requires a dual strategy, integrating both technological innovation and cultural-religious sensitivity. This study contributes to the discourse on digital finance by showing how religious values and ethical considerations influence consumer acceptance, offering insights for policymakers and financial institutions in designing inclusive digital ecosystems.